Bilingualism and hegemony : public discourse on Chinese language teaching in Singapore - Ee, Eileen Yan Li (2010)
This paper examines Singapore’s bilingual policy and recent changes in the teaching of Chinese in schools. In particular, a review of Chinese language teaching was undertaken following official criticisms of the traditional Chinese teaching methods. These criticisms stimulated the reproduction and contestation of official views in public discourse as seen in newspapers. By examining the respondents’ personal experiences in relation to Chinese language teaching, my argument is that the bilingual policy is a key part of the government’s agenda to achieve its objectives by using the implicit social status of English under the mask of bilingualism.